Pengaruh Budaya Kerja Dan Motivasi Kerja Terhadap Kinerja Guru ASN Di SMAN 4 Tebing Tinngi Dengan Komitmen Organisasi Sebagai Variabel Mediasi - Datliana, Datliana; Nababan, Rayu Veronika; Siregar, Aisyah (Economic Development Progress, 2025)
This research aims to determine the influence of work culture and work motivation on the performance of ASN teachers at SMAN 4 Tebing Tinngi with organizational commitment as a mediating variable. This research used a sample of 39 respondents, namely teachers at SMA Negeri 4 Tebing Tinggi. This research uses quantitative research with the help of the IBM SPSS 25.00 application. The results of hypothesis testing show that: 1) Work culture influences the performance of ASN teachers. 2) Work motivation influences the performance of ASN teachers. 3) Organizational commitment has no effect on the performance of ASN teachers. 4) Work culture has no effect on Organizational Commitment. 5) Work motivation influences Organizational Commitment. 6) Organizational commitment has no effect on the work culture and performance of ASN teachers. 7) Organizational commitment has no effect on work motivation and performance of ASN teachers.